SPECIALIZED RAPESEED CROP ROTATION SEQUENCES IN THE STEPPE CRIMEA - V. S. Pashtetsky; L. A. Radchenko; K. G. Zhenchenko (Зерновое хозяйство России)
The frequently changing market conditions of agricultural products require growing new and almost forgotten crops. Winter rapeseed is one of them. In the last decade its growing areas were increased to 14.000 ha on average, and in some years (2008) they were 30.000 ha. The main way to receive high yield of winter rapeseed in the Crimea is its proper place in the crop rotation sequences. The article gives the results of the study of winter rapeseed and wheat in the four specialized crop rotation sequences, where the rapeseed was sown in the bare (‘black’) fallow land and fallow winter wheat, and the wheat was sown after rapeseed, bare (‘black’) fallow and fallow wheat. The conducted analysis of weather conditions of the years showed, that during presowing and sowing periods there was the least amount of precipitations and it didn’t allow receiving the timely germination of rapeseed. The studying ancestors affected on the productivity of all crops participating in the crop rotation sequences. The rapeseed productivity during two crop rotation sequences (bare fallow) was 2.23 t/ha on average, but it was 1.60 t/ha in the direct reseeding. The productivity of the winter wheat sown after the rapeseed depended a lot on the ancestor: after the fallow rapeseed it was higher than in the direct reseeding (8% on average); after the rapeseed, sown after the wheat it was lower than in the direct reseeding (3%).